Tourism communities and social ties: the role of online and offline tourist social networks in building social capital and sustainable practice. Issue 2 (1st February 2017) - Dickinson, Janet E.; Filimonau, Viachaslau; Hibbert, Julia F.; Cherrett, Tom; Davies, Nigel; Norgate, Sarah; Speed, Chris; Winstanley, Chris
ABSTRACT: Mobile connectivity enables the adoption of new ways to connect with social networks which are changing how we might, and could, seek support. In the tourism domain we increasingly blend online and offline presence to engage with social networks in the spatial location, at a distance and across time. This paper explores the forms of community that exist in physical tourism contexts, contexts not previously analysed through a community lens, and explores how mobile technology is creating connections within and beyond existing social networks. It examines how sustainable tourism can be enhanced by mobile connectivity through new space–time practices and using ephemeral interpersonal relationships to harness niche groups to create bottom-up social systems interested in sharing experiences, ideas and resources. Special attention is given to the concept of gelling socialities which proposes a less ridged network structure, and to the need to understand the increasingly liquid social dynamics of mobile social interactions. The paper adds to the theories surrounding community, social ties and tourism's value to society. It draws on data from in-depth interviews undertaken while designing and testing a collaborative travel app. It contributes to growing research into the new technologies increasingly available for sustainable tourism marketing and implementation.